The world copper market: an economic analysis - Banks, Ferdinand E. (Cambridge, Mass., Ballinger Pub. Co., 1974)
This is a book of applied economics, its purpose is to give the reader a more or less complete insight into the functioning of the world copper market.
Bibliography: p. 141-143.
II 18/01/2019
Loans
Keywords: Copper industry and trade